Trends In Specialty Pharmacy Practice And Patient Care. A New Appraisal (Journal of Namibian Studies : History Politics Culture, 2022)
Specialty pharmacy practice has emerged as a critical component of modern healthcare, providing specialized medications and patient-centered care to individuals with complex medical conditions. This article examines key trends shaping the landscape of specialty pharmacy practice and patient care. It highlights the exponential growth of specialty pharmacy services driven by advancements in biotechnology, personalized medicine, and targeted therapies.The shift towards patient-centric care models, integration of technology, and data analytics to optimize treatment outcomes are explored. Regulatory challenges, including reimbursement complexities and collaborative care models, are discussed. Future opportunities for expansion and innovation, such as telepharmacy initiatives and value-based care models, are also explored. By understanding these trends, stakeholders in specialty pharmacy can better navigate the evolving healthcare landscape and enhance patient outcomes.